A review of the genus Sarbanissa Walker, 1865 in China, with description of a new species (Lepidoptera: Noctuidae: Agaristinae) - Wei, Fu-Hong; Kishida, Yasunori; Wang, Min (Zootaxa, 2019)
The genus Sarbanissa Walker in China is reviewed. A new species, S. pseudassimilis sp. nov., from Yunnan is described. This new species is diagnosed from S. assimilis Orhant. Moreover, here S. speciose Orhant is synonymized with S. transiens (Walker). A key to Chinese species and a checklist of Sarbanissa species of the world is provided.